Rekrutmen gubernur dan wakil gubernur D.I Yogyakarta dalam perspektif etika politik - Halili Halili (Universitas Negeri Yogyakarta, 2004)
Post implementation of UU No. 22/1999 (revised with UU No. 32/2004) about Local Government, recruitment mechanism of Governor and Vice Governor of D I Yogyakarta is being discussed around public opinions. They are polarized into two main groups; first, a group to agree and support recruitment through decision, and second, to agree and support a conventional mechanism of recruitment used in several provinces, namely election. This paper tries to analyze recruitment of Governor and Vice Governor of DI Yogyakarta on the perspective of political ethics. This perspective of analysis is based on two approaches. The first is formal-juridical approach; it means analysis about recruitment of Governor and Vice Governor of DI Yogyakarta and its congruency with the laws, which are valid. And the second is philosophy of power ethics; it includes resources, legitimacy, and implementation of power. Recruitment mechanism of Governor and Vice Governor of DI Yogyakarta finds legal and juridical justification in the positive laws; they are UUD 1945 (Constitution of RI), UU No. 22/1948, UU No. 3/1950, UU No. 5/1974, UU No. 22/1999, and UU No. 32/2004. In the other hand, according to political ethics of Thomas Aquinas about resources, legitimacy, and implementation of power, resources and legitimacy of power during recruitment of Governor and vice Governor of DIY get the right way in ethics manner. They correlate further with implementation of the power. So that, recruitment of Governor and vice Governor of DIY in perspective of political ethics is not merely matter of feudalism or monarchy, but it relates more with a matter of resources, legitimacy and implementation of power. If the power is correctly implemented, the resources and legitimacy will grow up, so does the contrary.